2012
DOI: 10.1149/2.038302jes
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Protection Performance of YSZ Coating on AA7075 Aluminum Alloy Prepared by Aerosol Deposition

Abstract: Yttria stabilized zirconia (YSZ) coating was deposited on AA7075 aluminum alloy by aerosol deposition (AD) at room temperature, and its electrochemical corrosion properties were investigated in 0.5 M H2SO4, 3.5 wt% NaCl, and 0.1 M KOH solutions. A crack-free, dense, and ∼5 μm thick YSZ coating on Al alloy was successfully obtained by AD method. The YSZ coating was polycrystalline and composed of ∼10 nm nanocrystallites. Potentiodynamic and electrochemical impedance spectroscopy (EIS) tests indicated that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Liang et al and Gao et al reported a similar mechanism for ZrO 2 metal oxide in basic solutions. Based on reactions –, the zirconate ions (HZrO 3 – ) that form under the alkaline conditions can act as a catalyst in the amine solution and facilitate proton transfer from MEAH + to MEACOO – . , Note that the OH – ion of ZrO 2 catalyst can partially react with the absorbed CO 2 and form HCO 3 – …”
Section: Promotion Mechanism Of Catalytic Co2 Desorptionmentioning
confidence: 99%
“…Liang et al and Gao et al reported a similar mechanism for ZrO 2 metal oxide in basic solutions. Based on reactions –, the zirconate ions (HZrO 3 – ) that form under the alkaline conditions can act as a catalyst in the amine solution and facilitate proton transfer from MEAH + to MEACOO – . , Note that the OH – ion of ZrO 2 catalyst can partially react with the absorbed CO 2 and form HCO 3 – …”
Section: Promotion Mechanism Of Catalytic Co2 Desorptionmentioning
confidence: 99%
“…Crack‐free, dense YSZ coatings with thicknesses between 4 and 5 μm and more than 100 μm were successfully deposited by AD. They offer corrosion protection on aluminum [ 263 ] and magnesium alloys [ 264 ] to improve the surface hardness of stainless steel [ 265 ] or as electrolytes in NO x sensors. [ 266 ] In contrast to alternative porous, screen‐printed electrolytes, lower noise, and higher sensitivities toward NO, as well as NO 2 , were observed for the dense coatings obtained by AD.…”
Section: Thermal Spray Technologiesmentioning
confidence: 99%
“…[17][18][19] Here, an aerosol is generated from powder and accelerated onto a substrate, where the powder particles break up and form a dense film. PAD is well established for a variety of different ceramic materials, like technical ceramics, [20][21][22][23] and ceramics for sensing and energy applications. [24] First commercial applications of PAD are already tested.…”
Section: Introductionmentioning
confidence: 99%